The economics of temporary migrations - Christian Dustmann; Joseph-Simon Görlach (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Many migrations are temporary - a fact that has often been ignored in the economic literature on migration. Such omission may be serious in that expected migration temporariness can impart a distinct dynamic element to immigrants' economic behavior, generating possible consequences for non-migrants in both home and host countries. In this paper we provide a thorough examination of the various aspects of temporary migrations that matter for the analysis of economic phenomena. We demonstrate the extent of temporary migrations in population movements. We show how temporariness can affect the various economic choices and how better data have improved both the measurement of nonpermanent migrations and the analyses of various aspects of migrant behavior. We propose a general theoretical framework for modeling temporary migration decisions, based on which we outline the various motives for temporariness while simultaneously reviewing related literature and available data sources. We discuss the possible consequences of migration temporariness for non-migrants in both home and host countries.
Keywords: F22; J61; O15; 330; immigrant behaviour; temporary migration